2021
DOI: 10.3390/ijerph18094938
|View full text |Cite
|
Sign up to set email alerts
|

Exergames in Childhood Obesity Treatment: A Systematic Review

Abstract: In the last decade, active video games (exergames) have been proposed in obesity prevention and treatment as a potential tool to increase physical activity. This review was aimed to assess the possible role of exergames in reducing weight-related outcomes among overweight/obese children and/or adolescents. The databases PubMed, Scopus, Web of Science and SPORTDiscus were interrogated to detect controlled studies involving healthy overweight/obese children and adolescents in interventions based exclusively on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…A strategy that employs and takes advantage of the available technologies to promote health [ 24 , 25 , 26 , 27 ] may be useful in promoting PA [ 26 ], and various programs worldwide use available technology to create active and physically challenging games (exergames) that encourage PA [ 28 ] Exergames have been found to promote physical activity, specifically among children with chronic conditions [ 29 , 30 ]. Incorporating such games in programs for children with overweight or obesity (OW/OB) may result in a greater reduction in BMI, higher adherence to PA [ 31 ], improved self-esteem [ 32 ], and a reduction in sedentary screen time [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strategy that employs and takes advantage of the available technologies to promote health [ 24 , 25 , 26 , 27 ] may be useful in promoting PA [ 26 ], and various programs worldwide use available technology to create active and physically challenging games (exergames) that encourage PA [ 28 ] Exergames have been found to promote physical activity, specifically among children with chronic conditions [ 29 , 30 ]. Incorporating such games in programs for children with overweight or obesity (OW/OB) may result in a greater reduction in BMI, higher adherence to PA [ 31 ], improved self-esteem [ 32 ], and a reduction in sedentary screen time [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating such games in programs for children with overweight or obesity (OW/OB) may result in a greater reduction in BMI, higher adherence to PA [ 31 ], improved self-esteem [ 32 ], and a reduction in sedentary screen time [ 33 ]. However, as concluded by a recent meta-analysis aimed to assess the possible role of exergames in reducing weight-related outcomes among OW/OB children, clear evidence about the effectiveness of exergames in determining weight loss in pediatric obesity is still lacking [ 26 ]. In addition to the established benefits of exergames, motivation to participate in PA is necessary to create lasting behavioral changes.…”
Section: Introductionmentioning
confidence: 99%
“…Calcaterra et al [154] also reported improvement in body composition, cardiorespiratory fitness, and metabolic profile through a supervised recreational training program of 12 weeks for sedentary obese children, including interactive video game exercises both during the supervised sessions and in a home-based setting. Other researchers found that the exergame treatment effects were related to PA level, BMI, and body fat reduction with specific exergames (e.g., Eyetoy, Kinect Sport) [149,150]. In a study with overweight children, Murphy et al [155] found that children in the tele-exercise group had a significant increase in total exercise time and VO 2 peak, and a decrease in body weight compared with control children.…”
Section: Before the Covid-19 Pandemicmentioning
confidence: 99%
“…Systematic reviews and meta-analyses indicate that exergames players can reach light to moderate intensity PA [149,150]. In 2013, a systematic review was performed by Lamboglia et al to analyze the use of exergaming against childhood obesity [151].…”
Section: Before the Covid-19 Pandemicmentioning
confidence: 99%
“…In recent years, researchers have become intrigued by the concept of active video games (exergames) which combine physical exercise with cognitively challenging tasks in an interactive game-based format [ 15 , 25 , 26 ]. Exergames, as opposed to traditional training programs, provide users with greater enjoyment and motivation through gamification mechanics [ 27 ], while also providing the adequate intensity of physical activity, such as ‘Just Dance’, which is considered to have a medium level of physical activity intensity [ 28 ].…”
Section: Introductionmentioning
confidence: 99%